Suzuki Piano Method and Flow Experience among Adult Piano Beginners: A Quasi-Experimental Study - Chen, Liu Xiao; Ta, Wang I; Yie, Wong Kwan (Harmonia: Journal of Arts Research and Education, 2023)
Although the Flow experience has been researched extensively in music education, there is limited investigation into exploring the link between the Suzuki piano method and Csikszentmihalyi’s flow theory. To address this gap, a quasi-experimental study was conducted to examine how the Suzuki piano method can promote the flow state of adult piano beginners. The study involved 36 participants assigned to either a treatment group or a control group. Both groups underwent an eight-week training program in Suzuki Piano Method and Conventional Group Piano Class respectively. After the program, participants from both groups underwent a post-training performance test and completed a survey, namely Learning and Performing Experience Scale (LPES), modified based on the Short Flow State Scale (S-FFS) by Martin and Jackson to examine their flow experience. The treatment group showed significantly higher flow experience levels than the control group, particularly in dimensions of Concentration, Unambiguous feedback, Timelessness, Loss of self-consciousness, Sense of control, Autotelic experience, and Challenge-skill balance. The findings suggested that the Suzuki piano method may promote flow experiences among adult beginners in piano learning. The implication of the study signified that the collaborative and interactive learning inherent in the method might be beneficial in achieving flow state and could be a consideration in conducting group piano classes.